Implementasi Manajemen Risiko Pada Produk Cicil Emas di PT Bank Syariah Indonesia, Tbk. KCP Sleman 2 - Wiwid Puspitasari1; Kusumawati, Rizqi Adhyka (Jurnal Aplikasi Bisnis, 2024)
Financing risk is often associated with failure to pay risk, which refers to bank losses when there are problems with the financing provided to customers. Risks that arise as the banking sector grows can have a negative impact on the company. One way to handle risk is to carry out good risk management. This research aims to determine the risks in the Gold Installment product at PT Bank Syariah Indonesia KCP Sleman 2, Tbk and the implementation of risk management in the Gold Installment product at PT Bank Syariah Indonesia KCP Sleman 2, Tbk. This report was written using data collection methods obtained through interviews and document study directly with PT Bank Syariah Indonesia KCP Sleman 2, Tbk. The results of this internship report show that there are several ways that PT Bank Syariah Indonesia KCP Sleman 2, Tbk does to anticipate risks with the initial steps, namely identifying risks, measuring risks, monitoring risks and handling risks in accordance with Financial Services Authority Regulation (POJK) No. .65/POJK.03/2016 concerning the Implementation of Risk Management for Sharia Commercial Banks and Sharia Business Units. PT Bank Syariah Indonesia KCP Sleman 2, Tbk has implemented these stages quite well so that it can prevent existing risks.